Battle hymns : the power and popularity of music in the Civil War - McWhirter, Christian (Civil War America (Series), 2012)
Music was everywhere during the Civil War. Tunes could be heard ringing out from parlour pianos, thundering at political rallies, and setting the rhythms of military and domestic life. With literacy still limited, music was an important vehicle for communicating ideas about the war, and it had a lasting impact in the decades that followed. Drawing on an array of published and archival sources, this book analyses the myriad ways music influenced popular culture in the years surrounding the war, and discusses its deep resonance for both whites and blacks, South and North.